A case for somatic practices as embodied mindfulness. Issue 1 (2nd March 2023) - Weber, Rebecca
Presenting convergences between mindfulness and somatic practices, this article makes a case for somatic practices as embodied mindfulness. It discusses historical origins as well as brief comments supporting some shared value systems and qualities espoused in both practices. After giving an overview of embodied cognition theory and the Interacting Cognitive Subsystems model, I trace how developing expertise in both somatic and mindfulness practices create the same cognitive repatterning to support the argument that somatics is a field of embodied mindfulness practices.